Transference and new records in Neoibidionini (Coleoptera, Cerambycidae) - Galileo, Maria Helena M.; Nascimento, Francisco E. De L.; Santos-Silva, Antonio (Zootaxa, 2018)
Compsibidion trinidadense (Gilmour, 1963) is transferred to Glomibidion Napp & Martins, 1985. Thirteen new records for species of Compsibidion Thomson, 1864, and Heterachthes Newman, 1840 are provided. Heterachthes delicatus Martins, 2009, formerly known only from Brazil (Caatinga Biome) is recorded for the first time for French Guiana (tropical moist forests). Additionally, three forgotten records are noted.